Characteristics of online behavior and structure of consumed content in Abakan adolescents of different age, groups and ethnicity - L. S. Evert; T. V. Potupchik; Yu. R. Kostyuchenko (Acta Biomedica Scientifica, 2022)
Background. The study of the prevalence and structure of various types of online behavior, the characteristics of the content consumed by adolescents of different age, sex and ethnic groups is an important area of scientific research.The aim. To study the features of online behavior and the structure of content consumed in Abakan adolescents of various age and sex groups and ethnicity (Russians and Khakasses).Materials and methods. 1400 adolescents of the city of Abakan (Republic of Khakassia) aged 12–18 were examined: 962 (68.7 %) Russians, 438  (31.3  %) Khakasses, 678 (48.4 %) boys and 722 (51.6 %) girls, aged 12–14 years – 39.8 % and 15–18 years – 60.2 %. The type of online behavior was verified using the Chen scale (CIAS). Emotional and behavioral disorders were diagnosed using the SDQ questionnaire. The indicators were compared in groups formed by sex, age and ethnicity. The data were processed using the Statistica 12.0 program (StatSoft Inc., USA).Results. It has been established that the prevalence and structure of online behavior among adolescents in Abakan depends on gender, age and ethnicity. Pathological Internet use (PIU) is more common among Khakasses, more often in the older age group. Regardless of ethnicity, maladaptive online behavior (pathological and maladaptive Internet use) is recorded more often among girls. In the structure of consumed content, gaming addiction prevails, social network addiction is in second place, and the proportion of mixed and undifferentiated Internet addiction is less. Dependence on online games prevails in boys, while dependence on social networks and undifferentiated internet addiction prevail in girls.Conclusion. One of the reasons for the greater prevalence of maladaptive online behavior among Khakasses may be the association of maladaptive Internet use with the presence of emotional disorders and behavioral problems that reach the borderline level and are causally significant factors in the development of Internet addiction. Adolescents with maladaptive online behavior, who have not yet reached the level of formed Internet addiction, are the target group requiring medical and psychological assistance.